The Impact of Promotional Strategies and Community Perceptions on Loan Uptake - Lestari, Ayu; Halim, Agus; Inzani SL, J. Fuji (Manunggal Halim Jaya, 2024)
This study aims to determine the effect of promotional variables and community perceptions on the decision to use loans at Karya Mandiri Cooperative, Central Mamuju Regency. The research method used is to use quantitative methods with primary data using a questionnaire. Respondents in the study were all customers who made loans at Karya Mandiri Cooperative, Central Mamuju Regency, the sample used was accidental sampling technique with a sample size of 30 respondents. The formula in this study uses multiple linear regression, validity test, reliability test, multiple linear regression, t test, and f test. The results in this study indicate that promotion and community perceptions have a positive and significant effect partially on the decision to use loans at Koperasi Karya Mandiri, Central Mamuju Regency. Promotion and community perception simultaneously have a significant effect on the decision to use loans at Karya Mandiri Cooperative, Central Mamuju Regency.